Association between subjective risk perception and objective risk estimation in patients with atrial fibrillation: a cross-sectional study. Issue 9 (25th September 2017) - Zweiker, David; Zweiker, Robert; Winkler, Elisabeth; Roesch, Konstantina; Schumacher, Martin; Stepan, Vinzenz; Krippl, Peter; Bauer, Norbert; Heine, Martin; Reicht, Gerhard; Zweiker, Gudrun; Sprenger, Martin; et al.
Abstract : Objective: Oral anticoagulation (OAC) is state-of-the-art therapy for atrial fibrillation (AF), the most common arrhythmia worldwide. However, little is known about the perception of patients with AF and how it correlates with risk scores used by their physicians. Therefore, we correlated patients' estimates of their own stroke and bleeding risk with the objectively predicted individual risk using CHA2 DS2 -VASc and HAS-BLED scores. Design: Cross-sectional prevalence study using convenience sampling and telephone follow-up. Settings: Eight hospital departments and one general practitioner in Austria. Patients' perception of stroke and bleeding risk was opposed to commonly used risk scoring. Participants: Patients with newly diagnosed AF and indication for anticoagulation. Main outcome measures: Comparison of subjective risk perception with CHA2 DS2 -VASc and HAS-BLED scores showing possible discrepancies between subjective and objective risk estimation. Patients' judgement of their own knowledge on AF and education were also correlated with accuracy of subjective risk appraisal. Results: Ninety-one patients (age 73±11 years, 45% female) were included in this study. Subjective stroke and bleeding risk estimation did not correlate with risk scores (ρ=0.08 and ρ=0.17). The majority of patients (57%) underestimated the individual stroke risk. Patients feared stroke more than bleeding (67% vs 10%). There was no relationship between accurate perception of stroke and bleeding risks and education level. However, we found a correlation between the patients' judgement of their own knowledge of AF and correct assessment of individual stroke risk (ρ=0.24, p=0.02). During follow-up, patients experienced the following events: death (n=5), stroke (n=2), bleeding (n=1). OAC discontinuation rate despite indication was 3%. Conclusions: In this cross-sectional analysis of OAC-naive patients with AF, we found major differences between patients' perceptions and physicians' assessments of risks and benefits of OAC. To ensure shared decision-making and informed consent, more attention should be given to evidence-based and useful communication strategies. Trial registration number: NCT03061123.